The Little Data Book on Information and Communication Technology 2015 - World Bank (Washington, DC, 2015)
This Little Data Book on Information and Communications Technology 2015 presents tables for over 213 economies showing the most recent national data on key indicators of information and communications technology (ICT), including access, quality, affordability, efficiency,sustainability, and applications.